2010
DOI: 10.1002/pam.20546
|View full text |Cite
|
Sign up to set email alerts
|

Growing exports by signaling product quality: Trade competition and the cross‐national diffusion of ISO 9000 quality standards

Abstract: Trade policy is an important topic in global public policy. It is recognized that trade is hampered when buyers have incomplete information about the offered products, a problem accentuated in the international markets by the physical and cultural distances between buyers and sellers.Buyers look for proxies to assess product quality, and exporters that can provide assurance about quality gain a competitive advantage. Our paper focuses on voluntary or private regulatory programs that have emerged as important i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 58 publications
(61 reference statements)
2
36
0
1
Order By: Relevance
“…A set of studies stress that there exists a positive correlation between the number of certificates and macro-economic variables such as the volume of direct overseas investment, the tendency to export to the EU and the country's public expenditure (see Table 1). Research by Cao and Prakash (2007) concluded that the adoption of ISO 9000 in a given country is likely to be encouraged if its salient export markets have high levels of ISO 9000 adoptions. Alburquerque et al (2007) pointed out that the diffusion of ISO 9000 is driven primarily by geography and bilateral trade relations.…”
Section: Iso 9000 and International Businessmentioning
confidence: 99%
“…A set of studies stress that there exists a positive correlation between the number of certificates and macro-economic variables such as the volume of direct overseas investment, the tendency to export to the EU and the country's public expenditure (see Table 1). Research by Cao and Prakash (2007) concluded that the adoption of ISO 9000 in a given country is likely to be encouraged if its salient export markets have high levels of ISO 9000 adoptions. Alburquerque et al (2007) pointed out that the diffusion of ISO 9000 is driven primarily by geography and bilateral trade relations.…”
Section: Iso 9000 and International Businessmentioning
confidence: 99%
“…Cao and Prakash (2011) suggest that trade competition induces firms to adopt ISO 9000, the most widely adopted voluntary quality certification program in the world, in order to signal commitment to quality and to increase exports. This logic can extend to ISO 14001 as well.…”
Section: (I) Investing Upmentioning
confidence: 98%
“…From a signaling perspective, the firms that have distant customers may choose to strategically implement institutional devices such as quality and environmental-related standards as this type of registration renders a firm's investments visible to the public and demonstrates the firm's contribution to satisfying the customers' quality and environmental expectations. Cao and Prakash (2011) show that the degree of trade competition increases the likelihood that firms join ISO 9000 standard while Bellesi et al (2005) and King et al (2006) illustrated how firms with potential foreign customers were more likely to registered with ISO 14001 standard. Moreover, as indicated by Grolleau et al (2012), there should be no influence of exports on workers' attitudes and behavior.…”
Section: The Empirical Modelmentioning
confidence: 99%